Investigating Jokowi’s ideological content through the Representation of the people of Indonesia in his political speeches - Suswanto Ismadi Megah S; Siti Noor Fazelah Mohd Noor; Azmi Abdul Latif (Development in Language Studies, 2021)
his paper aimed to discover President Joko Widodo (Jokowi)´s ideology via his political speeches delivered on the occasion of the Indonesian Independence Day every August 16, in 2015-219. The main objective of this study is to investigate Jokowi’s ideology by using the patterns of transitivity. This paper adopts Norman Fairclough (1995) Critical Discourse Analysis (CDA), which is analyzed with Halliday and Matthiessen (2014)’s Systematic Functional Linguistics (SFL) based on van Leeuwen’s theory of socio semiotics (2008). The political goal is realized through the representation of social actors in the political speech text. This study adopted three primary analytical tools of transitivity system, types of process, the grammatical participant roles, and the role allocation of social actors. The results showed that Jokowi represented the government in the grammatical participant role of the Actor in the material process. Moreover, Jokowi allocated the government as the most frequently represented in the activation role. His ideological content is embedded in his political speech text to build a positive image of his administration, considered as the acting taker to entrust that he and his staff worked hard. This was done to convince the audiences that his government is a working institution to gain support from his constituents. This study can be studied from another perspective in term of socio-economic perspective to unpack the ideological content behind his speeches. Therefore, it will be obtained wider understanding of his ideological stances inside his speeches.